2010
DOI: 10.1590/s1413-86702010000200011
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and microbiological characteristics of bloodstream infections in a tertiary hospital in Maceió, Alagoas, Brazil

Abstract: We observed the clinical and microbiological characteristics of several stages of bloodstream infections (BSI), as well as the mortality attributed to it in a tertiary hospital in the northeast of Brazil (in the city of Maceió, Alagoas). A prospective cohort of 143 patients who had at least one positive blood culture was enrolled in the study. Their clinical evolution was followed up for 30 days from October 2005 to December 2006. The relation among the qualitative variables was verifi ed through Chi-square te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
1
0
2
Order By: Relevance
“…Some authors have previously reported such change 8 and it has been proposed to be influenced by hospital clones being displaced by an increase in circulating community-derived clones having a multisensitivity pattern. 11 , 17 These clones’ participation has been identified in Colombia, North America and some Latin-American countries. A molecular study carried out in 2008 by Arias et al described similarities in the pattern of strains circulating in Colombia and the USA; this reinforced the need for establishing public health action in health care centres due to the risk of crossed dissemination in hospital services of such resistant strain coming from the community.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have previously reported such change 8 and it has been proposed to be influenced by hospital clones being displaced by an increase in circulating community-derived clones having a multisensitivity pattern. 11 , 17 These clones’ participation has been identified in Colombia, North America and some Latin-American countries. A molecular study carried out in 2008 by Arias et al described similarities in the pattern of strains circulating in Colombia and the USA; this reinforced the need for establishing public health action in health care centres due to the risk of crossed dissemination in hospital services of such resistant strain coming from the community.…”
Section: Discussionmentioning
confidence: 99%
“…En Latinoamérica, aunque no existe el mismo volumen de información, se han realizado estudios epidemiológicos de bacteriemia en programas de vigilancia nacional en Brasil (SCOPE) 19 , o a partir del programa internacional de vigilancia de resistencia antimicrobiana SENTRY 20 . También se han realizado estudios retrospectivos 21,22 , prospectivos de un solo centro 23,24 o en poblaciones específicas de infecciones nosocomiales o pacientes hospitalizados en UCI 25,26 . La mortalidad cruda está entre 28,8 y 40% 19,22 y la mortalidad atribuible entre 17 y 37,8% 2,22,24 .…”
unclassified
“…También se han realizado estudios retrospectivos 21,22 , prospectivos de un solo centro 23,24 o en poblaciones específicas de infecciones nosocomiales o pacientes hospitalizados en UCI 25,26 . La mortalidad cruda está entre 28,8 y 40% 19,22 y la mortalidad atribuible entre 17 y 37,8% 2,22,24 . En la mayoría de los estudios de Latinoamérica mencionados los microorganismos predominantes son bacilos gramnegativos, que representan entre 52 y 60% de los casos 19,27,28 ; pero en otros estudios, realizados en un solo centro en Argentina, predominaron las cocáceas grampositivas, entre 51,4 y 65,5% 22,29 .…”
unclassified